PC Towards Understanding Zimbabwe’s Competence-Based Science Curriculum and its Implications on the Study of Science, Technology, Engineering and Mathematics - Pinias Chikuvadze (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This study sought to gain an understanding of the Competence-Based Science Curriculum - CBSC as an approach that enhances students’ acquisition of Science, Technology, Engineering, and Mathematics - STEM knowledge, skills, and attitudes. In this conceptual paper, structural analysis formed the methodological framework that guided the cross-examination of the purposively selected research articles and document policies. Structural content analysis was used to interrogate the generated data. From the findings and discussion, it was noted that the CBSC was seen as an approach that is learner-centred and grounded in constructivism and perennialism philosophies. Thus, it promotes students’ interaction with their environment during STEM learning. Though CBSC can be well-planned, designed, and documented, it is marred with some challenges. From this, the discussion forwarded possible solutions geared towards equipping teachers with relevant knowledge, and skills to effectively implement the new approach in learning activities. From this discussion, it can be concluded that CBSC as an approach if effectively implemented can promote the acquisition of STEM knowledge, skills, and attitudes.